Physical, chemical, and biogeochemical parameters from a mesocosm experiment at the Sea Surface Facility (SURF), Wilhelmshaven, Germany, spring 2023 - Bibi, Riaz; Ribas-Ribas, Mariana; Jaeger, Leonie; Lehners, Carola; Gassen, Lisa; Cortés, Edgar; Wollschläger, Jochen; Thölen, Claudia; Waska, Hannelore; Zöbelein, Jasper; Brinkhoff, Thorsten; Athale, Isha; et al. (PANGAEA, 2025)
This collection (bundled publication) includes datasets from a mesocosm experiment conducted in spring 2023 at the Sea Surface Facility (SURF), Wilhelmshaven, Germany (53.5148° N, 8.1461° E). The experiment initiated a phytoplankton bloom under controlled conditions to examine surface ocean biogeochemistry and sea-surface microlayer (SML) processes. Daily samples were collected from the SML and underlying water (40 cm depth) and analyzed for physical, chemical, and biological parameters. Measurements include meteorological conditions (air temperature, solar irradiance, and albedo), surfactants, nutrients, pigments, particulate and dissolved organic carbon and nitrogen, and additional biogeochemical variables. These datasets provide environmental and biogeochemical context supporting studies on surface ocean processes and are described in detail in the related publication Bibi et al. (2025).
Keywords: BASS; biogeochemical processes; mesocosm experiment; mesocosm study; nutrients; organic matter; Phytoplankton bloom; sea-surface microlayer